1997
DOI: 10.1073/pnas.94.11.5778
|View full text |Cite
|
Sign up to set email alerts
|

Differential ability of T cell subsets to undergo activation-induced cell death

Abstract: Human T cell clones were analyzed for their susceptibility to activation-induced cell death (AICD) in response to CD3͞T cell receptor ligation. AICD was observed only in Th1 clones and was Fas-mediated, whereas Th2 clones resisted AICD. Analysis of a panel of Th0 clones, characterized by their ability to secrete both Th1 and Th2 cytokines, revealed that this subset included both AICD-sensitive (type A) and -resistant (type B) clones. Resistance to AICD by Th2 and Th0-type B clones was not due to lack of expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
127
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(141 citation statements)
references
References 68 publications
(57 reference statements)
12
127
2
Order By: Relevance
“…The observation that in the OVA-induced arthritis model, Hopx-deficient Th1 cells persist in spleen and lymph nodes, but not in the joint, the only place where the cationized antigen is displayed, argues that also in vivo Fas-mediated apoptosis may be involved in the elimination of Hopx-deficient Th1 cells. Th1 cells have been described to be more susceptible to Fas-mediated apoptosis than Th2 [14][15][16][17] and Th17 cells [18][19][20]. However, Th1 cells can be long lived and drive chronic inflammation [6][7][8][9][10][11][12][13], and can persist as effector/memory cells efficiently [24][25][26]65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that in the OVA-induced arthritis model, Hopx-deficient Th1 cells persist in spleen and lymph nodes, but not in the joint, the only place where the cationized antigen is displayed, argues that also in vivo Fas-mediated apoptosis may be involved in the elimination of Hopx-deficient Th1 cells. Th1 cells have been described to be more susceptible to Fas-mediated apoptosis than Th2 [14][15][16][17] and Th17 cells [18][19][20]. However, Th1 cells can be long lived and drive chronic inflammation [6][7][8][9][10][11][12][13], and can persist as effector/memory cells efficiently [24][25][26]65].…”
Section: Discussionmentioning
confidence: 99%
“…inflammatory bowel disease [6][7][8][9], uveitis [10], EAE [11,12] and arthritis [13]. In vitro, Th1 cells are much more sensitive to Fas-mediated apoptosis than Th2 or Th17 cells [14][15][16][17][18][19][20]. In vivo, however, effector/memory Th1 cells are abundant in chronically inflamed tissue [21][22][23] and persist over long time periods [24][25][26], suggesting that their sensitivity to Eur.…”
mentioning
confidence: 99%
“…It has been demonstrated that prolonged conjugation between effector T cells and APCs can result in apoptosis of T cells (31). Nevertheless, Th1 cells have been shown to be more susceptible to either Fas-induced (32)(33)(34) or NO-induced (35) apoptosis than Th2 cells. Because T cell lines used in the present study exhibited Th1 type, it is of interest to determine whether Th2 cells would survive better following infection.…”
Section: Discussionmentioning
confidence: 99%
“…With time and continued stimulation, the Fas-resistant phenotype reverses, and T cells become Fas-sensitive, without any change in the elevated level of Fas expression, perhaps as a result of IL-2R signaling and alterations in the levels of Bcl-xL and FLIP, although the precise mechanism remains uncertain [76], [129][130][131][132][133]. Additional reports suggest that Fas-sensitivity is modulated in anergic T cells, memory T cells, primed T cells and Th2 cells [134][135][136][137][138][139].…”
Section: Summary and Discussionmentioning
confidence: 99%